PEMBINAAN APARATUR PEMERINTAHAN DALAM PELAKSANAAN TUGAS TUGAS ORGANISASI DI BAGIAN UMUM SEKRETARIAT KANTOR BUPATI KABUPATEN DELI SERDANG - Eko Surya (PERSPEKTIF, 2015)
In an effort to improve performance, local governments do things that lead to the achievement of the organization at the local authority as mandated in the legislation. Absolute internal improvements done as a provision in the service eksternal.Tujuan this study to see how peminaan conducted by the local government of Deli Serdang Regency to the general secretariat of the apparatus at the office of Regent of Deli Serdang. This type of research is qualitative descriptive approach through data collection using literature study and interview. The results showed there are a variety of training programs undertaken by the government of Deli Serdang area in order to increase the capacity of the performance capability on the part of public servants including the secretariat office of Regent of Deli Serdang.